2011
DOI: 10.1111/j.1365-313x.2011.04664.x
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of CENH3 in Arabidopsis reduces mitotic divisions and causes sterility by disturbed meiotic chromosome segregation

Abstract: SUMMARYThe histone H3 variant (CENH3) of centromeric nucleosomes is essential for kinetochore assembly and thus for chromosome segregation in eukaryotes. The mechanism(s) that determine centromere identity, assembly and maintenance of kinetochores are still poorly understood. Although the role of CENH3 during mitosis has been studied in several organisms, little is known about its meiotic function. We show that RNAi-mediated CENH3 knockdown in Arabidopsis thaliana caused dwarfism as the result of a reduced num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 59 publications
2
101
0
Order By: Relevance
“…We observed that in a population of knl2 mutant plants (;60 plants), ;30% of plants show reduced growth (Figure 4) and a phenotype similar to that of the cenH3 RNAi transformants (Lermontova et al, 2011a), while growth rate of another 70% of plants was only slightly reduced or did not differ from the wild type. Such phenotypic variation within a population of homozygous mutants was also observed for epigenetic mutants of Arabidopsis, such as met1-3 (Mathieu et al, 2007) and ddm1, the latter showing a gradual accumulation of developmental aberrations during inbreeding (Vongs et al, 1993;Kakutani et al, 1996).…”
Section: Cenh3 Assembly Is Regulated At the Transcriptional Levelmentioning
confidence: 84%
See 1 more Smart Citation
“…We observed that in a population of knl2 mutant plants (;60 plants), ;30% of plants show reduced growth (Figure 4) and a phenotype similar to that of the cenH3 RNAi transformants (Lermontova et al, 2011a), while growth rate of another 70% of plants was only slightly reduced or did not differ from the wild type. Such phenotypic variation within a population of homozygous mutants was also observed for epigenetic mutants of Arabidopsis, such as met1-3 (Mathieu et al, 2007) and ddm1, the latter showing a gradual accumulation of developmental aberrations during inbreeding (Vongs et al, 1993;Kakutani et al, 1996).…”
Section: Cenh3 Assembly Is Regulated At the Transcriptional Levelmentioning
confidence: 84%
“…Therefore, we analyzed the expression of the histone methyltransferase encoding genes SUVH4, SUVH2, and SUVH9 in 14-d-old seedlings of Arabidopsis wild type, knl2 mutants, and cenH3 RNAi transformants (Lermontova et al, 2011a) by real-time RT-PCR ( Figure 6A). We found that expression of SUVH4 and SUVH9 was reduced in the knl2 mutant to 50% of the wild-type level, but expression of SUVH2 was only slightly lower than in the wild type ( Figure 6A).…”
Section: A Regulatory Network For Cenh3 Assembly In Arabidopsismentioning
confidence: 99%
“…S8). In addition, the abundance of a centromerespecific histone H3 variant (CENH3), required for centromere function and chromosome segregation (34), was reduced in the mutant background (SI Appendix, Fig. S9F).…”
Section: Resultsmentioning
confidence: 99%
“…If left unchecked, neocentromeres result in the loss of chromosome integrity, which leads to diseases, including cancer, in humans (1,38). Below a certain threshold of cellular CenH3 levels, cells cease mitosis in Arabidopsis (39). Similarly, in human cells, the posttranslational reduction of CenH3 levels results in senescence, where cells lose the ability to divide, likely to prevent defective mitoses (7), which may be a process that requires p97.…”
Section: Discussionmentioning
confidence: 99%